2015
DOI: 10.1371/journal.pone.0129016
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Regulatory Motif Discovery Identifies Significant Motifs in Promoters of Five Classes of Plant Dehydrin Genes

Abstract: Plants accumulate dehydrins in response to osmotic stresses. Dehydrins are divided into five different classes, which are thought to be regulated in different manners. To better understand differences in transcriptional regulation of the five dehydrin classes, de novo motif discovery was performed on 350 dehydrin promoter sequences from a total of 51 plant genomes. Overrepresented motifs were identified in the promoters of five dehydrin classes. The Kn dehydrin promoters contain motifs linked with meristem spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 130 publications
(146 reference statements)
3
17
0
Order By: Relevance
“…Interestingly, HvDHN5 expression was not significantly altered with elevated HvCBF14 levels. This may be related to the fact that the HvDHN5 gene belongs to the K n class of dehydrins, which respond to frost and drought, but they are not regulated by the light [37,39,52]. In the present experiment, we also observed that the HvDHN5 gene did not respond differently at different light intensities.…”
Section: The Expression Of Hvcbf14 and Its Target Genes Hvcor14b And supporting
confidence: 53%
“…Interestingly, HvDHN5 expression was not significantly altered with elevated HvCBF14 levels. This may be related to the fact that the HvDHN5 gene belongs to the K n class of dehydrins, which respond to frost and drought, but they are not regulated by the light [37,39,52]. In the present experiment, we also observed that the HvDHN5 gene did not respond differently at different light intensities.…”
Section: The Expression Of Hvcbf14 and Its Target Genes Hvcor14b And supporting
confidence: 53%
“…We found a number of dehydrin-like genes that were up-regulated from paradormancy to endodormancy, and these genes provide good models for how different combinations of cis -regulatory elements can lead to different patterns of gene expression. For example, Zolotarov and Stromvik (2015) identified 14 conserved motifs in 350 dehydrin promoters from 51 plant genomes, many of which were similar to motifs that were overrepresented in our differentially expressed genes, as well as in genes that have been associated with responses to cold, dehydration, ABA, and light.…”
Section: Discussionmentioning
confidence: 77%
“…Similar to our findings, Bassett et al [14] and Wisniewski et al [15] observed that no DRE elements were found in positive sense in the PpDhn2 promoter and suggested that the absence of this cis-element was related to the lack of expression in response to cold. However, other reports have confirmed the presence of one DRE/CRT element in the promoter region of the Y n SK n dehydrin class, which includes PpDhn2 [75]. In spite of this observation, it is known that Y n SK n dehydrins are not expressed in response to cold.…”
Section: Discussionmentioning
confidence: 93%
“…García-Bañuelos et al [76] concluded that MdDhn, which shows great similarity with PpDhn2, was accumulated after a period of acclimation in apple trees. Based on that, Zolotarov and Strömvik [75] affirmed that cold-induced expression of Y n SK n -type dehydrins would not be detected in some cases because of a limited time of exposure to low temperature. So that, the presence of the DRE and LTRE elements found in the anti-sense position in our individuals could have some effect in the expression of PpDhn2 in a possible response to cold.…”
Section: Discussionmentioning
confidence: 99%